Exploring the long-term safety of asenapine in adults with schizophrenia in a double-blind, fixed-dose, extension study - Durgam S (Dove Medical Press, 2017)
Suresh Durgam,1 Ronald P Landbloom,2 Mary Mackle,2 Xiao Wu,1 Maju Mathews,3 Henry A Nasrallah4 1Allergan Inc, Jersey City, 2Merck, Whitehouse Station, 3Forest Research Institute (now Allergan), Jersey City, NJ, 4Saint Louis University School of Medicine, St Louis, MO, USA Purpose: The primary objective of this study was to assess long-term safety with sublingual asenapine 2.5 or 5 mg twice daily (BID) in patients with schizophrenia.Patients and methods: Actively treated patients on asenapine 2.5 mg BID, asenapine 5 mg BID, or olanzapine 15 mg once daily (QD) who completed a 6-week randomized, double-blind, placebo- and olanzapine-controlled study continued lead-in treatment in this 26-week, multicenter, double-blind, double-dummy, olanzapine-controlled Phase IIIB extension study; placebo patients were assigned to asenapine 2.5 mg BID treatment. Safety analyses were based on the all treated set (patients who received one or more doses of extension trial medication); change from baseline analyses used the acute study baseline. Treatment-emergent adverse events (TEAEs) and changes in laboratory parameters were monitored; weight change for asenapine versus olanzapine was the key secondary objective. Descriptive statistics were used; weight change was analyzed using a mixed-model repeated-measure approach.Results: Of the 120 patients in the all-treated set, 60% completed treatment (asenapine 2.5 mg BID 66.1% overall, asenapine 5 mg BID 52.4%, olanzapine 15 mg QD 56.3%). The incidence of TEAEs was higher for placebo patients from the lead-in study who switched to asenapine 2.5 mg BID for extension treatment (71.0%) versus patients continuing asenapine 2.5 mg BID (38.7%), asenapine 5 mg BID (38.1%), or olanzapine 15 mg QD (25.0%). The most common TEAE (≥5% in every group) was worsening of schizophrenia. Least squares mean change in body weight from the acute study baseline to week 26 was +0.6 kg for overall asenapine 2.5 mg BID, +0.8 kg for asenapine 5 mg BID, and +1.2 kg for olanzapine 15 mg QD. There were no clinically relevant changes in metabolic parameters; values were generally similar across treatment groups.Conclusion: Asenapine 2.5 mg BID and 5 mg BID were generally well tolerated in long-term treatment. Weight gain was less for overall asenapine 2.5 mg BID and 5 mg BID than for olanzapine 15 mg QD. Keywords: asenapine, schizophrenia, long-term, safety, weight, olanzapine